2022
DOI: 10.3389/fpubh.2022.1043216
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation and suicide attempts in healthcare professionals during the COVID-19 pandemic: A systematic review

Abstract: BackgroundCOVID-19 has caused a series of economic, social, personal, and occupational consequences that may affect the mental health of healthcare workers (HCWs), with the consequent risk of developing suicidal ideation and behaviors.ObjectivesThe aim of this study was to identify the main risk factors that may predispose HCWs to suicidal ideation and suicide attempts during the COVID-19 pandemic.MethodsA systematic review of studies published between January 2020 and August 2022 was conducted following the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 71 publications
1
18
0
4
Order By: Relevance
“…Similarly, a study by Gasteiger et al [49] found that depression and anxiety had been most negatively afected during the frst ten weeks of social distancing during the COVID-19 pandemic. All these negative emotions can cause problems at the psychological level and, of course, in work carried out by the nursing staf, bringing about errors, and malpractice, which would also infuence patient safety [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study by Gasteiger et al [49] found that depression and anxiety had been most negatively afected during the frst ten weeks of social distancing during the COVID-19 pandemic. All these negative emotions can cause problems at the psychological level and, of course, in work carried out by the nursing staf, bringing about errors, and malpractice, which would also infuence patient safety [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a systematic review of suicidal ideation among HCWs during the COVID-19 pandemic, 11 studies assessed suicide attempts using the same criteria as in the present study (i.e., item nine scores of PHQ-9 ≥ 1). The proportion of HCWs at high risk of suicidal ideation ranged from 2.4% to 18.6% [ 6 ]. These results indicate psychological impacts and burdens among HCWs unexpectedly exposed to major COVID-19 outbreaks at workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the COVID-19 pandemic has worsened the mental health of healthcare workers (HCWs) [ 4 , 5 , 6 , 7 , 8 ]. HCWs, such as nurses and nursing home staff, were essential to the COVID-19 public health response.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations